Islamic fiqh and technology: Implications and influence in the digital era - Suherman, Sunandar (Maliki Interdisciplinary Journal, 2024)
In the rapidly advancing digital era, technology has transformed various aspects of human life, including religious contexts such as Islam. This article explores how Islamic jurisprudence (fiqh) relates to technology usage in the digital age. We delve into the implications and influences arising from the intersection of Islamic jurisprudence and technology, while seeking solutions to address the challenges. In the realm of technology use, Islam emphasizes ethical principles that Muslims should follow. Despite the convenience and comfort provided by technology, adhering to religious boundaries remains essential. For instance, responsible and judicious use of social media is encouraged, avoiding slander, hatred, or privacy violations. Islamic jurisprudence provides guidance on various technological contexts, including financial matters and worship practices. However, reconciling centuries-old fiqh with rapidly evolving technology poses challenges, necessitating adaptation by scholars and Muslim intellectuals to provide relevant guidance.